Efficient up-conversion in CsPbBr3 nanocrystals via phonon-driven exciton-polaron formation - Abbas, Abdullah S.; Li, Beiye C.; Schaller, Richard D.; Prakapenka, Vitali B.; Chariton, Stella; Bian, Daqian; Engel, Gregory S.; Alivisatos, A. Paul (Nature communications, 2025)
Lead halide perovskite nanocrystals demonstrate efficient up-conversion, although the precise mechanism remains a subject of active research. This study utilizes steady-state and time-resolved spectroscopy methods to unravel the mechanism driving the up-conversion process in CsPbBr 3 nanocrystals. Employing above- and below-gap photoluminescence measurements, we extract a distinct phonon mode with an energy of ~7 meV and identify the Pb-Br-Pb bending mode as the phonon involved in the up-conversion process. This result was corroborated by Raman spectroscopy. We confirm an up-conversion efficiency reaching up to 75%. Transient absorption measurements under conditions of sub-gap excitation also unexpectedly reveal coherent phonons for the subset of nanocrystals undergoing up-conversion. This coherence implies that the up-conversion and subsequent relaxation is accompanied by a synchronized and phased lattice motion. This study reveals that efficient up-conversion in CsPbBr 3 nanocrystals is powered by a unique interplay between the soft lattice structure, phonons, and excited states dynamics. Here, the Authors show that up-conversion in CsPbBr3 nanocrystals arises from an interaction between soft lattice vibrations and excited states, with a specific phonon mode enabling coherent and highly efficient up conversion process.